From Kitchen Waste to Medical Hope:: The Onion Peel Discovery - Sekarwangi, Marlita; Abidah, Nisa; Maftukhah, Fani Nur; Fahrani, Almayra Khanza; Sari, Ratna Mustika (BIODIVERS - BIOTROP Science Magazine, 2025)
Dengue Hemorrhagic Fever (DHF), a severe and sometimes life-threatening disease spread by Aedes mosquitoes, often leads to a sharp drop in platelet counts and triggers intense immune reactions called cytokine storms. There has been no specific cure; a reality that triggers us to explore natural remedies that might help, one of which comes from an unexpected source: yellow onion peels. How do the yellow onion peels work against dengue virus? Let’s continue reading.